2019
DOI: 10.3390/w11102079
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Turbulent Horseshoe Vortex System in Front of a Vertical Circular Cylinder in Open Channel

Abstract: A turbulent horseshoe vortex (HV) system around a wall-mounted cylinder in open channel is characterized by random variations in vortex features and an abundance of vortex interactions. The turbulent HV system is responsible for initiating the local scour process in front of the cylinder. The evolution of the turbulent HV system is investigated statistically and quantitatively with time-resolved particle image velocimetry. The cylinder Reynolds numbers of the flow are 8600, 10,200, and 13,600, respectively. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Recently, Li et al (2018) [24] used the high-resolution PIV system to study the flow characteristics induced by the horseshoe vortex in front of the pier. Similar experimental studies can be found by Chen et al (2019) [25] who systematically analyzed the transient evolution process of horseshoe vortex. The previous relevant PIV studies are mainly confined on the flow of a pier mounted on a flatbed without scour hole, which can be regarded as the initial scour state.…”
Section: Introductionsupporting
confidence: 76%
“…Recently, Li et al (2018) [24] used the high-resolution PIV system to study the flow characteristics induced by the horseshoe vortex in front of the pier. Similar experimental studies can be found by Chen et al (2019) [25] who systematically analyzed the transient evolution process of horseshoe vortex. The previous relevant PIV studies are mainly confined on the flow of a pier mounted on a flatbed without scour hole, which can be regarded as the initial scour state.…”
Section: Introductionsupporting
confidence: 76%
“…In Figure 10(c), CRVP and similar mushroom vortex 1 can be detected. A mushroom vortex is often realized behind concave walls or along streamlines with a curvature form [36]. By reducing the perforation area distribution and pores'vertical distance (M5 scenario), the GÖrtler instability changes into the large dual mushrooms.…”
Section: The Surface Line Integral Convolution At X/d =mentioning
confidence: 99%
“…(c) Upstream cross-sectional profile of the frontal scour hole indicating internal differentiation and positions of primary horseshoe vortex (HV1) in back-flow mode, and secondary horseshoe vortex (HV2) (not to scale) [Colour figure can be viewed at wileyonlinelibrary.com] located close to the obstacle base. During incision, HV1 sinks into the frontal scour hole and extends down to S b , where it promotes sediment mobilization by saltation and rolling (Chen et al, 2019;Dargahi, 1990;Dey & Raikar, 2007). Upstream of HV1, a smaller and less coherent vortex (HV2) is located within the outer region of the frontal scour hole (Figures 1c and 2).…”
Section: Morphodynamic Processes At Instream Obstaclesmentioning
confidence: 99%
“…The largest and most stable vortex is denoted as the primary horseshoe vortex (HV1) and is located close to the obstacle base. During incision, HV1 sinks into the frontal scour hole and extends down to S b , where it promotes sediment mobilization by saltation and rolling (Chen et al, 2019; Dargahi, 1990; Dey & Raikar, 2007). Upstream of HV1, a smaller and less coherent vortex (HV2) is located within the outer region of the frontal scour hole (Figures 1c and 2).…”
Section: Introductionmentioning
confidence: 99%